A complexidade do processo de sucessão em empresas familiares: um estudo de caso da libel linhares distribuidora de bebidas em Rosário – Maranhão. - Santos, Marcos Aurélio Araújo (2006)
The requirement for the market of competitive companies comes if becoming each bigger time, in sight of the constant changes that happen at every moment in the globalizado world. To manage a company is a complex task, and this task becomes still more delicate when it is about a familiar company. To manage a company where the employees participate of day-by-day of the family, for they will belong it, can many of the times confuse the constitution of these spaces, generating in the enterprise environment crises whom they can have origin from the incapacity of the manager in separating two environments, or same of the difficulty in separating its emotivo side of familiar matrix of the professional activities of the company. Ally to the these difficulties appears one of the biggest problems of the familiar enterprise, the question of the succession, moment that is crucial for many companies and reflects in its permanence in the same market or in its dissolution and bankruptcy. The concern with the successory planning is born from there, still not treated with the had importance that must to it by some companies. A Study of Case is presented here, of a company who comes if developing in efficient way, however could is well better if it was not passing for a crisis in the succession, resulted of the absence of a planning for its founders. One searchs here to portray the problem of the succession, and thus to demonstrate that this process must be thought and be analyzed, if possible since the first years of life of the company, since enough period has for this elaboration.